Application of the Radial Mode Matching Method to Determine the Resonant Frequency of a Cone Shaped Dielectric Resonator - Krzysztof Derzakowski (IEEE, 2021)
The paper presents an application of the radial mode matching method to determine the resonant frequency of cone-shaped dielectric resonators. The results of calculations with the use of the developed computer program are presented. The accuracy of the resonator cone projection was investigated taking into account a different number of regions into which the conical resonator was divided. The influence of the number of the considered waveguide modes on the accuracy of the calculation of the resonance frequency was also analyzed. The results of the calculations were compared with the results obtained with the QuickWave electromagnetic simulator. These results are convergent, which proves the correctness of the adopted assumptions and the full usefulness of the radial mode matching method for calculating the resonance frequencies of the cone-shaped dielectric resonator.